Regeneration of Bitter Gourd (Momordica charantia L.) from Leaf Segments and Root Tips - Al Munsur, MAZ; Haque, MS; Nasiruddin, KM; Hasan, MJ (Progressive Agriculture, 2013)
Experiments were carried out to study the callus induction and subsequent plantlet regeneration ability of leaf segments and root tips of bitter gourd. A combination of 1.0 mg L-1 2,4-D and 1.0 mg L-1 BAP produced the highest percentage of callus in leaf segments (78.75%) and 1.0 mg L-1 2,4-D combined with 0.5 mg L-1 BAP produced the highest callus frequency in root tips (72.5%). Using the combination of BAP at 2.0 mg L-1 and NAA at 0.3 mg L-1 improved the callus induction frequency (80.00%) in root tips. Root tips showed better response than leaf segments in callus induction. Leaf segments and root tips had equal percentage (65.0) of shoot regeneration upon culture of the calli on medium with 2.0 or 2.5 mg L-1 BAP with 0.2 mg L-1 IAA. The highest length (3.95 cm) of shoot from leaf segments was recorded with 2.5 mg L-1 BAP, 0.5 mg L-1 IBA and 0.2 mg L-1 GA3. The highest number of roots (6.75) and root length (2.45 cm) were found in 3.0 mg L-1 BAP with 0.1 mg L-1 NAA in root tips. The callus formation and regeneration ability of the explants have the potential for use in future biochemical studies and genetic improvement of bitter gourd. DOI: http://dx.doi.org/10.3329/pa.v18i2.17457 Progress. Agric. 18(2): 1 - 9, 2007